Hubungan Tingkat Pengetahuan Dengan Keaktifan Kader Dalam Menjalankan Posyandu Balita Di Desa Pacalan Wilayah Kerja Puskesmas Plaosan - Farma Handika, Farinda; , Agus Sudaryanto, S.Kep., Ns., M.Kes; , Enita Dewi, S.Kep.,Ns.MN (2016)
Posyandu success can not be separated from the hard work of cadres who volunteered to manage neighborhood health center in each region. Lack of training and coaching to improve skills that are adequate for the cadres led to a lack of understanding of duty cadres, lack of information and lack of coordination between the officers and cadres in Posyandu kegiatanan implementation can result in low levels of the presence of children under five years (toddlers) to Posyandu. This study aimed to analyze the relationship between the level of knowledge with the liveliness of cadres in Posyandu implement Pacalan Toddler Village Puskesmas Plaosan. The study design was cross with cross-sectional approach. The population in this study were all cadre's Village Puskesmas Pacalan Plaosan Magetan. The sampling technique used is total sampling, so that the whole population is used as a sample. The analytical tool used by the Nonparametrik Rank Spearman. The survey results revealed that: The knowledge level cadres in Posyandu toddler running in the village Puskesmas Pacalan Plaosan evenly. Liveliness cadres in Posyandu toddler running in the village Puskesmas Pacalan Plaosan included in kateogi inactive. There are between level of knowledge with the liveliness of cadres in Posyandu toddler running in the village Puskesmas Pacalan Plaosan (p = 0.036).